2018
DOI: 10.14814/phy2.13823
|View full text |Cite
|
Sign up to set email alerts
|

Activin subfamily peptides predict chronological age in humans

Abstract: Loss of muscle mass and function are a well‐defined aspect of human aging from the 3rd decade of life, which result in reduced independence and increased mortality. The activin family of peptides contains several endocrine factors (activin A, myostatin, growth and differentiation factor 11 [GDF11]) that may play roles in changes in muscle mass and the aging process, however, it may be simplistic to consider aging as a result of a single peptides changes. Thus, we aimed to examine changes in activin family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Importantly also, in the ageing population, reduced physical activity and increase in sedentary time are typically observed ( Lindsay et al, 2019 ). Furthermore, no difference in muscle mass or fat mass was seen in our study population, unlike that witnessed in wider society ( Volpi et al, 2004 ; Barrios-Silva et al, 2018 ). By studying highly active ageing cohorts, we can separate physiological differences of ageing from inactivity induced changes ( Harridge and Lazarus, 2017 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Importantly also, in the ageing population, reduced physical activity and increase in sedentary time are typically observed ( Lindsay et al, 2019 ). Furthermore, no difference in muscle mass or fat mass was seen in our study population, unlike that witnessed in wider society ( Volpi et al, 2004 ; Barrios-Silva et al, 2018 ). By studying highly active ageing cohorts, we can separate physiological differences of ageing from inactivity induced changes ( Harridge and Lazarus, 2017 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Although we did not observe any effect on circulating myostatin levels, Fortetropin has been shown to decrease circulating myostatin levels ( 7 , 16 ) in healthy subjects. The consensus of published data suggests an age associated decrease in circulating myostatin levels ( 17 , 18 ), although the role of myostatin in aging has not been established and the functional interpretation of circulating myostatin remains uncertain. We found here that in a group of healthy older subjects, circulating myostatin levels were positively associated with muscle protein FSR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, contradictory findings have been made regarding the relationship between serum myostatin and muscle function. Some studies found increased circulating myostatin concentrations in patients with better muscle function or physical performance [ 80 , 81 , 83 , 84 , 87 ], and several indicated such a relationship to be more apparent in the male population [ 85 , 93 ], while others did not show any clear correlation between those parameters [ 82 , 88 , 89 , 92 , 94 ].…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
“…A study of intramuscular mRNA and protein expression showed that although myostatin gene expression was higher in older adults, no difference in myostatin protein content was found [ 74 ]. Results of three studies indicated that serum myostatin concentration rises with age [ 79 , 84 , 94 ]. In their cross-sectional study, Bergen et al, used a new mass spectrometry-based assay to show that circulating myostatin, acting as a homeostatic regulator of muscle mass in males, could be found in the highest concentration in young men, and decreased with age, while in women, it increased as a function of age, acting as a possible mediator of sarcopenia [ 85 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%